An analysis of the electron trajectory in the vicinity of GaAs quantum dot - Hanafi Ithnin,; M., Khalid Kasmin; A., Radzi Mat Isa; A., Shaari; R., Ahmed (Universiti Kebangsaan Malaysia, 2014)
Quantum dots being an interesting class of nanostructures are considered potential prototype systems for novel nano-devices such as single electron transistor (SET). Here in this research, we present an analysis of the electron trajectory in the vicinity of gallium arsenide (GaAs) quantum dot. To perform this study, DFT based methodology is employed to optimize structure of quantum dot and determining the electrostatic potential around the dot. Under the influence of obtained electrostatic potential, trajectory of the moving electron towards the dot is investigated. The results showed that GaAs quantum dot have negative and positive potential surfaces that influence the electron interaction with the dot. These results motivate the development of SET electrode channel where the electron moves towards the dot on the surface with positive potential rather than negative potential surface.